Optimization of the Effect of Electropolishing's Current Density and Time on Roughness, Microstructure and Corrosion Resistance - Sutarno; Bambang Widyanto; E.P. Syuryana; Soleh Wahyudi; Fikri Septian Nurul Bayan; Camalia Bani Rachma; Gusti Verhan Pratama; Riskamti; Ariq Akmal Muwaffaq (JEMMME (Journal of Energy, Mechanical, Material, and Manufacturing Engineering), 2021)
The surface roughness of medical, pharmaceutical, food, and beverage equipment in direct contact with materials and products plays an important role in product quality, hygiene, equipment corrosion, and ease of cleaning. The high surface roughness is feared as a place for the accumulation of process residues, products, and nesting of microbes such as pathogenic bacteria that degrade product quality. The purpose of this research is to investigate the parameters of the electropolishing process, namely the electric current density and the time of the electropolishing process. The electrolyte solution is a mixture of 35% sulfuric acid and 51% phosphoric acid with the electropolishing process temperature being maintained at 50°C, using stainless steel as cathode, and the material being processed is AISI 316L. Characterization of electropolishing results includes roughness, microstructure, and corrosion resistance.